Modulações anatômicas, bioquímicas e fotossintéticas mediadas por Azospirillum brasilense inoculado via semente e pulverização foliar em milho - Battistus, Andre Gustavo (2019)
The use of plant growth promoting bacteria has been highlighted due to the search for sustainable technologies that could increase the world agricultural production, being able to emphasize the genus Azospirillum as the most widespread. Rhizospheric bacteria habit also presents ability to colonize shoot tissues, opening doors for distribution through sprays in foliar tissues, providing effects similar to those triggered by inoculations via seed. The objective of this study was to elucidate the biochemical, photosynthetic, anatomical, morphophysiological and yield effects in corn inoculated with Azospirillum brasilense applied by seed and/or foliar spraying. Five trials were conducted, four at field level and another under controlled substrate conditions to evaluate the treatments: control; A. brasilense seed inoculation; A. brasilense foliar spraying; and seed inoculation allied to foliar spraying of A. brasilense. In a controlled substrate experiment, at V12 stage, with inducing water restriction, and at the R3 stage, with adequate water availability, gas exchange evaluations were carried out throughout the day, together with collect of leaf samples for biochemical analysis of the activity of antioxidant enzymes, and analysis of cell turgor and stability of membranes in V12 stage. It was also determined the content of photosynthetic pigments, gas exchange as a function of luminosity(V12 and R3) and concentration of CO2(R3). In the V12stage, collected samples for anatomical determinations inherent to conducting vessels, stomata and lignin, and evaluated the of Chlorophyll a fluorescence. At the end of the cycle, SPAD index was determined. The fieldlevel trials were carried out in two harvests and sites, aiming to evaluate production components and crop productivity. Volume, root mass and total mass were increased by inoculation + spraying. The use of A. brasilense increased the number and internal diameter of vessels of the root metaxylem. The protoxylem vessels had increased transport area, and the phloem had elevated number, diameter and area. Number of phloem vessels was raised by the spraying bacteria. The adaxial epidermis and leaf limbus thickened, just as the number of stomata as increased. The root lignin was reduced by the inoculations but stimulated in the leaves by the combination of the applications. Spraying increased the efficiency of photosystem II in harnessing electrons and passing them more efficiently to the net assimilation of CO2. The lack of water reduces photosynthesis, but A. brasilense sustains high levels of leaf water contents, greater transpiration facilitating the contribution of CO2 and avoiding greater reductions in photosynthesis. The antioxidant activity is driven by both applications, especially in the high light moments, continuing until dusk. The inoculation and spraying made possible greater photosynthesis in high luminosities. Activity of the carboxylic enzymes improved under high concentrations of intercellular CO2. Photosynthesis and transpiration were higher in leaves near the spike when sprayed A. brasilense. The pigment content did not change during the cycle, but all the treatments provided a stay-green effect at his end. There were no effects on productivity. The results reaffirm the role of A. brasilense in the greater soil exploration and indicate its stimulation in the use of environmental resources, increase of photosynthesis and stay-green effect, promoted by inoculation, and with a better performance by A. brasilense foliar spraying.